2021
DOI: 10.1186/s40168-021-01176-w
|View full text |Cite
|
Sign up to set email alerts
|

The Metaproteomics Initiative: a coordinated approach for propelling the functional characterization of microbiomes

Abstract: Through connecting genomic and metabolic information, metaproteomics is an essential approach for understanding how microbiomes function in space and time. The international metaproteomics community is delighted to announce the launch of the Metaproteomics Initiative (www.metaproteomics.org), the goal of which is to promote dissemination of metaproteomics fundamentals, advancements, and applications through collaborative networking in microbiome research. The Initiative aims to be the central information hub a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 15 publications
(10 reference statements)
0
55
0
Order By: Relevance
“…We still do not fully understand if distinct construction strategies produce databases that perform differently on biological systems of variable complexity since the most thorough evaluations described in this paper were done only on mice and human gut samples [88] . Community efforts such as the Metaproteomics Initiative [160] , which, for example, recently carried out an interlaboratory comparison of metaproteomic workflows [19] , may represent an excellent mechanism to evaluate the impact of database construction approaches on metaproteomics.…”
Section: Perspectives and Concluding Remarksmentioning
confidence: 99%
“…We still do not fully understand if distinct construction strategies produce databases that perform differently on biological systems of variable complexity since the most thorough evaluations described in this paper were done only on mice and human gut samples [88] . Community efforts such as the Metaproteomics Initiative [160] , which, for example, recently carried out an interlaboratory comparison of metaproteomic workflows [19] , may represent an excellent mechanism to evaluate the impact of database construction approaches on metaproteomics.…”
Section: Perspectives and Concluding Remarksmentioning
confidence: 99%
“…Existing studies have shown that intestinal microbiota is closely related to the occurrence and development of diabetes, hypertension, cardiovascular disease, tumors, etc., because of its important role in human health, it is also called the human body's forgotten organs [9,[30][31][32][33][34][35][36]. In addition, the intestinal microbiota is huge, and it contains about 100 times the number of genes in the human genome, so it is also known as the second genome of the human body [17,37,38]. The main proportion of bacteria are Firmicutes and Bacteroides, which account for more than 90%.…”
Section: Overview Of the Intestinal Microbiotamentioning
confidence: 99%
“…In order to further examine the functions of these microbial groups, multi-omics research is more used. Metatranscriptome is used to detect the structure of functionally active microbial populations at the transcriptional level [51,52]; metaproteome is used to detect protein information translated by functionally active microbial populations [17,53]; metabolome is used to detect metabolite information produced by functionally active microbial populations [46,54].…”
Section: Overview Of the Intestinal Microbiotamentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the interpretation of data acquired on a whole animal or its gut must also take into account the presence of the associated microbiome. With the holobiont concept in mind, the molecular description of such samples requires new conceptual advances combining the best of the worlds of proteogenomics and metaproteomics [12,13]. The environment in which we live is the most precious element to perpetuate life and its protection a noble cause.…”
Section: Introductionmentioning
confidence: 99%